HUBUNGAN ANTARA KADAR HEMOGLOBIN DENGAN KADAR KREATININ SERUM PENDERITA PENYAKIT GINJAL MENAHUN (KRONIS) - Rosnety, .; M Arif; Hardjoeno . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Chronically Kidney Disease (CKD) is the health problem of society worldwide, included Indonesia which its amount will increase.Clinical manifestation often following CKD is anaemia which will be severe with the increasing of serum creatinine values. To determinefrequent distribution of anaemia degree and assessing relationship between haemoglobin (Hb) and creatinine concentration in CKDpatients. Retrospective Descriptive Study in CKD patients with anaemia. In the period of May-September 2006, from 50 CKD patientsat the Department of Internal Medicine, Dr.Wahidin Sudirohusodo Hospital Makassar, 38 patients (76%) suffered severe anaemia(Hb < 8 g/dl). Mean value of Hb was 6,85 g/dl and serum creatinine concentration was 11.89 mg/dl. There was a significantrelationship between increasing of serum creatinine and decreasing of Hb (p = 0,013). Majority of CKD patients suffered from severeanaemia, there was relationship between increasing of serum creatinine and decreasing of Hb. To make routine blood tests and bloodsmears in CKD patients is needed, with large of samples to assess the relationship between Hb and serum creatinine.